Kajian Distribusi Pendapatan Petani Padi Ciherang (Oryza sativa) di Kecamatan Haruyan Kabupaten Hulu Sungai Tengah Provinsi Kalimantan Selatan - Ahmad Suhaimi; Nurlenny Khatimah (Rawa Sains: Jurnal Sains STIPER Amuntai, 2014)
This study aims to determine income, and income distribution of rice farmers Ciherang paddy in Haruyan District Hulu Sungai Tengah Regency Kalimantan Selatan Province. Research carried out for 3 months from June to August 2014. Research The use descriptive research design, analysis units studied were rice farmers Ciherang .This method of sampling is done with purposive sampling method. The results showed that, farmers' net income ranging from Rp 84 097 - Rp 16,992,279. The results of the analysis of income distribution Ciherang rice farmers through the calculation of figures obtained Gini ratio 0.499, this hi menunjukkandistribusi Ciherang rice farmers' income is at the level of the gap being. Inequality of income distribution is suspected because of a less than optimal use of land, lack of use of a tool or machine that is appropriate and lack of extension's role in providing guidance to farmers how good and proper cultivation.